Políticas públicas y control de convencionalidad (Tema Central) - Salvador Monteros, Ana Michelle (2022)
Public policies are actions executed by states to satisfy situations understood as public problems. The control of conventionality is a state obligation, contracted in good faith by ratifying the American Convention on Human Rights and recognizing the contentious jurisdiction of the Inter-American Court. Both issues have the State as the main character, but they are rarely dealt with together. This article explores the relationship between these two issues in guaranteeing rights and will be analyzed through the study of the Guzmán Albarracín case, which raises State obligations in the area of public policies to prevent and eradicate sexual violence in the educational sphere. In order to achieve this goal, four study sections are proposed: Public policies, taking into account their formulation, implementation and evaluation; the human rights approach; the Guzmán Albarracín case and the public policies related to sexual violence in the educational sphere in Ecuador; the control of conventionality, which studies the doctrine and main functions of this institute; the control of conventionality in the Ecuadorian case, based on the study of the 2008 Constitution with its particular characteristics, The latter is not only a doctrinal development embodied in these lines, but is a transversal axis in this paper.